AMIC Seminar on Training Needs in the Use of Media for Distance Education in Asia, Singapore, Jun 8-11, 1987 : [contents] - AMIC Seminar on Training Needs in the Use of Media for Distance Education in Asia, Singapore, Jun 8-11, 1987. (2009)
Accepted version